Unveiling a sudden unexplained death case by whole exome sequencing and bioinformatic analysis. Issue 4 (26th February 2020) - Modena, Martina; Castiglione, Vincenzo; Aretini, Paolo; Mazzanti, Chiara M.; Chiti, Enrica; Giannoni, Alberto; Emdin, Michele; Di Paolo, Marco
Abstract: Background: Sudden unexplained death (SUD) refers to cases of sudden death where autopsy fails to identify any cardiac or extracardiac underlying cause. Guideline‐directed standard genetic testing identifies a disease‐causing mutation in less than one‐third of cases of SUD. Conversely, whole exome sequencing (WES) may provide the key to solve most cases of SUD even after several years from the subject's death. Methods: We report on a case of sudden unexpected death of a 37‐year‐old male, with inconclusive autopsy conducted 14 years ago. A recent reevaluation through WES was performed on DNA extracted from left ventricular samples. A multiple step process including several "in silico" tools was applied to identify potentially pathogenic variants. Data analysis was based on a 562 gene panel, including 234 candidate genes associated with sudden cardiac death or heart diseases, with the addition of 328 genes highly expressed in the heart. WebGestalt algorithms were used for association enrichment analysis of all genes with detected putative pathogenic variants. Results: WES analysis identified four potentially pathogenic variants: RYR2:c.12168G>T, TTN:c.11821C>T (rs397517804), MYBPC3:c.1255C>T (rs368770848), and ACADVL:c.848T>C (rs113994167). WebGestalt algorithms indicated that their combination holds an unfavorable arrhythmic susceptibility which conceivably caused the occurrence of the events leading to our subject's sudden death. Conclusion: Associating WES technique with online prediction algorithms may allow the recognition of genetic mutations potentially responsible for otherwise unexplained deaths. Abstract : We report on a case of sudden unexpected death of a 37‐year‐old male, with inconclusive autopsy conducted 14 years ago, where recent reevaluation through whole exome sequencing (WES) and WebGestalt algorithms allowed the recognition of four genetic mutations (RYR2‐K4056N, TTN‐R3941C, MYBPC3‐R419C, and ACADVL‐V283A) potentially responsible for the subject's sudden death.